A qualitative analysis on family physician\'s program to identify the causes as well as challenges of the failure of program accomplishment - Hossein Alaie; Niloufar Amiri Ghale Rashidi; Mojtaba Amiri (Tehran University of Medical Sciences, 2020)
Background: The Family Physician Program, one of the most important efforts of the Iran health system to establish a referral system, was developed and implemented in several provinces, but it faced challenges due to several reasons that prevented the programchr('39')s progress. So This study was conducted to analyze the family physician program to identify the causes and challenges of the program failure. Materials & Methods: This retrospective study of policy analysis is a qualitative study with Purposive sampling. Semi-open interviews and document analysis were used for data collection. Data analysis was performed through thematic analysis in the policy triangle framework using MAXQDA software. Results: According to the study framework, the challenges of the Family Physician Program in the context are conflict of interest, dependency of plans to oneself, instability in management and plans, insufficient attention to culture, resources, and infrastructure. In terms of content include disproportionate executive approach, Lack of localization, selection of inappropriate tools, insufficient transparency, and ambiguity in goals, tasks, and responsibilities; The challenges of the process were examined based on the policy cycle. Conclusion: The implementation of the family physician program is influenced by cultural, social, political, managerial, and economic factors. As the Ministry of Health officials has re-introduced this crucial program, reviewing the content and methods of program implementation seems necessary.